The oscillations of the dynamical system with hysteresis characteristics excited by stochastic parameter and forces. I. - Menh, Nguyen Cao (Vietnam Journal of Mechanics, 1979)
In this paper, the nonlinear mechanical system with imperfect elastic characteristics excited by parameter and external forces in the form of stationary Gaussian stochastic processes is considered. Heuristic and enveloped methods in a similar way as in the paper [5] are used. The closed differential equation system with constant coefficients is established to determine the statistical characteristics of solution process.